Sub-zero cold tolerance of Spartina pectinata (prairie cordgrass) and Miscanthus × giganteus: candidate bioenergy crops for cool temperate climates - Friesen, Patrick C. (J Exp Bot, 2015)
Miscanthus × giganteus grown in cool temperate regions of North America and Europe can exhibit severe mortality in the year after planting, and poor frost tolerance of leaves. Spartina pectinata (prairie cordgrass), a productive C(4) perennial grass native to North America, has been suggested as an alternative biofuel feedstock for colder regions; however, its cold tolerance relative to M. × giganteus is uncertain. Here, we compare the cold tolerance thresholds for winter-dormant rhizomes and spring/summer leaves of M. × giganteus and three accessions of S. pectinata. All genotypes were planted at a field site in Ontario, Canada. In November and February, the temperatures corresponding to 50% rhizome mortality (LT(50)) were near −24°C for S. pectinata and −4°C for M. × giganteus. In late April, the LT50 of rhizomes rose to −10°C for S. pectinata but remained near −4°C for M. × giganteus. Twenty percent of the M. × giganteus rhizomes collected in late April were dead while S. pectinata rhizomes showed no signs of winter injury. Photosynthesis and electrolyte leakage measurements in spring and summer demonstrate that S. pectinata leaves have greater frost tolerance in the field. For example, S. pectinata leaves remained viable above −9°C while the mortality threshold was near −5°C for M. × giganteus. These results indicate M. × giganteus will be unsuitable for production in continental interiors of cool-temperate climate zones unless freezing and frost tolerance are improved. By contrast, S. pectinata has the freezing and frost tolerance required for a higher-latitude bioenergy crop.